2020 IEEE 17th International Symposium on Biomedical Imaging (ISBI) 2020
DOI: 10.1109/isbi45749.2020.9098384
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Edition of Ultrasound Images via Sketch Guided Progressive Growing GANS

Abstract: Ultrasound (US) is widely accepted in clinic for anatomical structure inspection. However, lacking in resources to practice US scan, novices often struggle to learn the operation skills. Also, in the deep learning era, automated US image analysis is limited by the lack of annotated samples. Efficiently synthesizing realistic, editable and high resolution US images can solve the problems. The task is challenging and previous methods can only partially complete it. In this paper, we devise a new framework for US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…After removing duplicates, 197 articles were screened to assess their eligibility. Subsequently, 19 studies fulfilled the proposed eligibility criteria and were included in this review 13–31 . A graphical representation of the screening process can be found in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After removing duplicates, 197 articles were screened to assess their eligibility. Subsequently, 19 studies fulfilled the proposed eligibility criteria and were included in this review 13–31 . A graphical representation of the screening process can be found in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The median size of the training datasets reported in the articles was 1565 images. Similar to conditional generation, preprocessing methods, such as cropping, scaling, flipping, and rotation, were used to augment the dataset; however, three studies failed to report any preprocessing performed on the training data 23,25,27 . Four studies reported the use of generative models previously proposed in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep attention networks have also been proposed for improved segmentation performance in US imaging, such as the attention-guided dual-path network [53] and a U-Net-based network combining a channel attention module and VGG [54]. A contrastive learning-based framework [55] and a framework based on the generative adversarial network (GAN) [56] with progressive learning have been reported to improve the boundary estimation in US imaging [57]. The critical issues resulting from the instability of the viewpoint and cross-section often become apparent when the clinical indexes are calculated using segmentation.…”
Section: Algorithms For Us Imaging Analysismentioning
confidence: 99%
“…To enable GANs to study images of different rock types simultaneously and enhance the representativeness of generated samples according to user-defined properties, we leverage the GANs in a conditioning manner, which was originally proposed by Mirza and Osindero (2014). In this study, we adopt progressively growing GANs as a basic architecture (Karras et al 2017), which has demonstrated excellent performance in image synthesis (Liang et al 2020;Wang et al 2018), and has been successfully applied in geological facies modeling (Song et al 2021). Inspired by the work of generating MNIST digits based on class labels with conditional GANs (Mirza and Osindero 2014), we make the rock type as one of the conditional information, aiming to generate samples with respect to a specified rock type.…”
Section: Introductionmentioning
confidence: 99%